Natural Lipstick Formulation Based on Monascus Purpureus Extract: Variation of Beeswax–Candelilla Wax and Evaluation of Antioxidant Activity - Rohmawati Hidayah; Iif Hanifa Nurrosyidah (International Journal of Health Engineering and Technology, 2026)
Lip colorants are cosmetic preparations used to color the lips with an artistic touch, thereby enhancing the aesthetic aspect of facial makeup. This study aims to formulate a lipstick using a natural dye derived from angkak (Monascus purpureus), with variations in the wax base using beeswax and candelilla wax, to produce a safe, comfortable, and long-lasting lipstick product. Methods: This experimental study was conducted in four stages: Stage one, Extraction of Natural Dye: The natural dye from Monascus purpureus was extracted using the maceration method with 96% ethanol as the solvent. Stage two, Lipstick Formulation: Three formulas were developed—F1, F2, and F3—with the following beeswax to candelilla wax ratios: F1 (2 : 3.57), F2 (3.57 : 2), F3 (2.78 : 2.78). Stage three, Physical Quality Evaluation: The formulations were evaluated for organoleptic properties, homogeneity, pH, melting point, spreadability, hardness, and stability. Stage four, Antioxidant Activity Test: To assess the antioxidant potential of the natural dye used. Results: All lipstick formulas exhibited good physical stability and met the required physical quality standards for organoleptic properties, homogeneity, pH, melting point, spreadability, and stability. However, a significant difference was found in the hardness test results, influenced by the varying concentrations of beeswax and candelilla wax. Conclusion: Variations in the concentration of beeswax and candelilla wax affect the physical quality, particularly the hardness of the lipstick. The best hardness result was obtained in Formula 1 (F1), with a beeswax concentration of 2% and candelilla wax concentration of 3.57%.